2007
DOI: 10.1063/1.2643073
|View full text |Cite
|
Sign up to set email alerts
|

120 Hz pulse tube cryocooler for fast cooldown to 50K

Abstract: A pulse tube cryocooler operating at 120Hz with 3.5MPa average pressure achieved a no-load temperature of about 49.9K and a cooldown time to 80K of 5.5min. The net refrigeration power at 80K was 3.35W with an efficiency of 19.7% of Carnot when referred to input pressure-volume (PV or acoustic) power. Such low temperatures have not been previously achieved for operating frequencies above 100Hz. The high frequency operation leads to reduced cryocooler volume for a given refrigeration power, which is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…This would enable miniaturization of the regenerator and the development of microcryocoolers for on-chip cryogenic cooling. We have experimentally demonstrated this theoretical prediction on a mesoscale cooler [8]. Conventional regenerative cryocoolers operating at 80 K use stainless steel wire screens as the regenerative material.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This would enable miniaturization of the regenerator and the development of microcryocoolers for on-chip cryogenic cooling. We have experimentally demonstrated this theoretical prediction on a mesoscale cooler [8]. Conventional regenerative cryocoolers operating at 80 K use stainless steel wire screens as the regenerative material.…”
Section: Introductionmentioning
confidence: 94%
“…Hence, the Reynolds number also varies along the length of the regenerator. Micro regenerative cryocoolers that operate at high frequency (120-1000 Hz) have an optimum gas cross-sectional area to mass flow (equal to 1/ρU m ) in the range of 0.02-0.07 m 2 s kg −1 [8,9], and for a hydraulic diameter less than 30 µm, the region of interest of the Reynolds number is in the range between Re ∼ 50 and 250.…”
Section: Definitions and Designmentioning
confidence: 99%
“…Radebaugh and O'Gallagher [19] showed that high efficiency can be maintained at higher frequencies by simultaneously making the following changes to the operating conditions and the regenerator geometry: (a) decrease regenerator volume, (b) decrease hydraulic diameter, and (c) increase average pressure. Experiments with a 120 Hz pulse tube cryocooler verified that high efficiency can be maintained when the modifications discussed above are made [20]. FIGURE 8 shows calculated results for the cold-head efficiency of a 50 K regenerative cryocooler operating at 60 Hz and at 120 Hz.…”
Section: Higher Frequency and Pressure In Regenerative Cryocoolersmentioning
confidence: 99%
“…Increasing the frequency to about 1 kHz, the tube radius of the pulse tube can be made considerably smaller, allowing the miniaturization of the cryocooler. Design rules for efficient high frequency operation of a regenerator was reported by Radebaugh and O'Gallagher, 13 which, was experimentally verified on a macroscale by Vanapalli et al 14 The next step is to realize an efficient high frequency pressure oscillator to drive the microcold stage.…”
Section: Introductionmentioning
confidence: 99%